PENGGUNAAN HORMON PERTUMBUHAN REKOMBINAN TERHADAP PERTUMBUHAN IKAN SELAIS (Ompok hypopthalmus) - Maulina Sawitri; Usman Muhammad Tang; Henni Syawal (Fakultas Perikanan dan Kelautan, Universitas Riau, 2018)
This study was aimed to determine the best dose of recombinant growth hormone on the growth of selais fish (Ompok hypopthalmus). This study used a complete randomized desigh with one factor that is recombinant growth hormone dose and 3 repetition. The dose given were 0 mg/kg, 6 mg/kg, 12 mg/kg, 18 mg/kg and 24 mg/kg. The results showed that addition of rElGH at dose of 12 mg/kg were the best dose for selais fish growth’s parameters; absolute length growth (3,60± 0,6 cm), absolute weight growth (3,85 ± 0,46 g), daily growth rate (5,56 ± 0,32 %), food convertion ratio (1,10 ± 0,12), protein and fat retention (46,73 ± 21,34 % and 103,83 ± 21,43 %). The highest level of glycogen muscle (22,43 ± 0,61 mg/g) was found in addition of rElGH at dose of 18 mg/kg.